Management of Adverse Effects from Medications Used to Treat Substance Use Disorders - Calles, Joseph L. (Current Psychopharmacology, 2018)
Background: Substance use disorders (SUDs) are an increasing problem worldwide. In the United States, there is currently an “opioid epidemic,” primarily initiated by the over-prescription of opioid medications, barriers to continued access to those same medications, and the eventual procurement of illegal opioids to prevent withdrawal. In addition to the diversion of prescription opioids (especially oxycodone and fentanyl), other, more powerful opioids (e.g., carfentanil) have found their way to the street. Of especial concern is the number of adolescents who have access to legal- but diverted- or illegal drugs, as they are at risk for developing SUDs. Clinicians in various treatment settings (such as primary care offices, emergency departments, and mental health clinics) may lack the knowledge and training to safely and effectively treat patients who have SUDs. Fortunately, there are several pharmacologic agents that are approved for the treatment of opioid, alcohol and nicotine use disorders in adults and several agents have been explored to treat cannabis use disorder. To date, none of these medications have been approved for those indications in adolescents, although they can be-and are- used off-label in that patient population. All medications can be associated with adverse events, which are of particular concern in younger patients. Objective: To address the most common adverse effects from medications used to treat substance use disorders, and to offer suggestions regarding management of those unwanted effects. Method: The method utilized was PubMed search, from January 1, 2002 through November 1, 2017, with cross-referencing medications used to treat SUDs, adverse events and their treatment. Results: The substances addressed in this article (opioids, alcohol, tobacco and cannabis) are the most commonly abused in the general population, and are the most likely to be associated with adverse medical, psychiatric, social, financial and legal consequences. Medications used to treat opioid, alcohol, tobacco and cannabis use disorders are described, along with important adverse effects and their treatment. Conclusion: Given that there is no “drug of choice” to treat any given SUD, the selection of agent will depend on the patient's personal characteristics (e.g., age, gender, medical status, degree of social support, etc.) and preferences, and the prescriber's knowledge, comfort, and experience regarding the available medications. The pharmacotherapy of SUDs should always be accompanied by psychosocial therapies.
Keywords: treatment